Identifying the Source of Unknown Microcystin Genes and Predicting Microcystin Variants by Comparing Genes within Uncultured Cyanobacterial Cells - Allender, Christopher J. (American Society for Microbiology (ASM), 2009)
While multiple phylogenetic markers have been used in the culture-independent study of microcystin-producing cyanobacteria, in only a few instances have multiple markers been studied within individual cells, and in all cases these studies have been conducted with cultured isolates. Here, we isolate and evaluate large DNA fragments (>6 kb) encompassing two genes involved in microcystin biosynthesis (mcyA2 and mcyB1) and use them to identify the source of gene fragments found in water samples. Further investigation of these gene loci from individual cyanobacterial cells allowed for improved analysis of the genetic diversity within microcystin producers as well as a method to predict microcystin variants for individuals. These efforts have also identified the source of the novel mcyA genotype previously termed Microcystis-like that is pervasive in the Laurentian Great Lakes and they predict the microcystin variant(s) that it produces.